Correction: Drif et al. Anti-Inflammatory and Cancer-Preventive Potential of Chamomile (Matricaria chamomilla L.): A Comprehensive In Silico and In Vitro Study. Biomedicines 2024, 12, 1484 - Assia I. Drif; Rümeysa Yücer; Roxana Damiescu; Nadeen T. Ali; Tobias H. Abu Hagar; Bharati Avula; Ikhlas A. Khan; Thomas Efferth (Biomedicines)
There was an error in the original publication [...]